Você Vê Minha Aura, de Que Cor Ela É? o Ver e o Ouvir em Arthur Bispo do Rosario - Almeida, Ana de (2020)
Arthur Bispo do Rosario's production is unique in its complexities. In view of its representation of the world, possessed by the field of art, it has unique characteristics that can be theorized by seeing and listening. Seeing in Bispo would be the visual